Multilingual dictionary of Slavic somatic phrasemes - Masha Bekjkovikj; Elena Markova; Katerina Zdravkova (Faculty of Computer Science and Engineering, 2016)
Phrasemes are multi-word expressions and utterances with a distinctive syntax and semantics. Due to the ethnological diversity, they are language specific and in many occasions, the exact translation of a phraseme existing in one source language doesn’t occur in other target languages, no matter their linguistic and cultural similarity. The presentation of source phrasemes, their meaning and examples in a form of an interactive and searchable multilingual dictionary is a good starting point for further linguistic research. This paper presents the creation of such a dictionary, its basic functionalities, the process of its development, and finally illustrates its performance according to assigned user roles. The paper ends with the further stages of its development.
Keywords: somatic phrasemes, morphological search, stemming, search